Driving cooperative actions: A multimethod study of the temporal duration of unilateral commitments. Issue 3 (20th September 2021) - Paraskevas, John‐Patrick; Eckerd, Stephanie; Grimm, Curtis M.
Abstract: Previous research demonstrates numerous benefits of mutual commitments between parties. However, less is understood about the effect of unilateral commitments, when one party (the committer ) makes a relationship‐specific investment without an established current or forthcoming reciprocal commitment by the other party (the recipient ). This problem is particularly relevant in the supply chain management domain, where organizations often make investments in their supply chain partners, and frequently assume great risks in doing so. To help organizations understand how they can initiate unilateral commitments to their benefit, we develop theory regarding the outcomes of unilateral commitments based on their temporal duration. We evaluate our hypothesis using data collected from three distinct studies, each using different methodologies and samples: a laboratory experiment of graduate students, a vignette experiment of operations management practitioners, and a secondary data analysis of baseball contracts. We find compelling support that unilateral commitments of shorter duration successfully drive recipient cooperative behavior; however, a significant decrease in recipient cooperation results from longer term unilateral commitments. Our research contributes broadly to the literature on unilateral commitments, and in particular its manifestation within supply chain management, where this research stands to make substantial impact due to the prevalence of unilateral commitments.